Redox and Calcium Alterations of a Müller Cell Line Exposed to Diabetic Retinopathy-Like Environment - Rosato, Clarissa; Bettegazzi, Barbara; Intagliata, Pia; Balbontin Arenas, Maria; Zacchetti, Daniele; Lanati, Antonella; Zerbini, Gianpaolo; Bandello, Francesco; Grohovaz, Fabio; Codazzi, Franca (Frontiers in Cellular Neuroscience, 2022)
Diabetic retinopathy (DR) is a common complication of diabetes mellitus and is the major cause of vision loss in working-age population. Although DR is traditionally considered a microvascular disease, an increasing body of evidence suggests that neurodegeneration is an early event that occurs even before the manifestation of vasculopathy. Accordingly, attention should be devoted to the complex neurodegenerative process occurring in diabetic retina, also considering possible functional alterations in non-neuronal cells, such as glial cells. In this work we investigate functional changes in Müller cells, the most abundant glial population present within the retina, under experimental conditions that mimic those observed in DR patients. More specifically, we investigated on the Müller cell line rMC-1 the effect of high glucose, alone or associated with activation processes and oxidative stress. By fluorescence microscopy and cellular assays approaches, we studied the alteration of functional properties, such as reactive oxygen species production, antioxidant response, calcium homeostasis and mitochondrial membrane potential. Our results demonstrate that hyperglycaemic-like condition per se is well-tolerated by rMC-1 cells but makes them more susceptible to a pro-inflammatory environment, exacerbating the effects of this stressful condition. More specifically, rMC-1 cells exposed to high glucose decrease their ability to counteract oxidative stress, with consequent toxic effects. In conclusion, our study offers new insights into Müller cell pathophysiology in DR and proposes a novel in vitro model which may prove useful to further investigate potential antioxidant and anti-inflammatory molecules for the prevention and/or treatment of DR.